PERWUJUDAN PRINSIP DESAIN AKTIF PADA REVITALISASI RUANG TERBUKA PUBLIK KOTA, Studi Kasus : Lingkungan Saparua Park, Kota Bandung: https://doi.org/10.25124/idealog.v4i1.1589 - Irfandian, Raden Rangga Ilham (Ide dan Dialog Desain Indonesia (Idealog), 2019)
The advancement of development, technology and urban culture, globally has produced various positive and negative impacts on environmental conditions and human life. One of the negative impacts is the declining public health factor. At present, the main cause of death in urban communities is cardiovascular disease caused by people's lifestyles that are minimal to carry out physical activity or sedentary lifestyle. Based on these phenomena there are various design principles for the physical environment, one of which is the principe of Active Design. The Active Design can be understood as a set of principles in designing the physical setting of the environment so that it can stimulate its users to carry out physical activity without them knowing it. The Active Design Principle is seen as having a significant impact on increasing public health factors when applied to the urban public spaces. In line with these thoughts, in the city of Bandung there has been a phenomenon of improvement in the city's public space, one of which is the revitalization of Saparua Park. There is an interesting thing about the revitalization of the Saparua Park environment, namely the incorporation of two dominant concepts in one unit of the environment, thematic garden concepts for recreational needs and the concept of sports complexes for the needs of public sports facilities. This research is a qualitative-descriptive study which contains the formulation of Active Design indicators in the urban public space based on literatures. Then evaluate the physical settings of Saparua Park environment after revitalization based on Active Design indicators that have been formulated. Produced an understanding of the extent to which the principles of Active Design materialize in the physical environment of Saparua Park, the potential for future development and any manifestation that can be used as an example for designing urban public spaces elsewhere. Keywords : Active Design, Urban Public Space, Public Health, Revitalization